Allium Crop Science: Recent Advances 2002
DOI: 10.1079/9780851995106.0329
|View full text |Cite
|
Sign up to set email alerts
|

Sulphur compounds in alliums in relation to flavour quality.

Abstract: Although it is realized that flavour is the result of a multifaceted interaction among many different compounds, this chapter reviews the sulfur compounds that give alliums their characteristic flavours and odours.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
101
0

Year Published

2006
2006
2023
2023

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 96 publications
(104 citation statements)
references
References 0 publications
3
101
0
Order By: Relevance
“…The EPY value, shoot and root TSC, and S content of shoots and roots of spring onion all increased with increasing S supply level in the substrate (Table 3). These results were expected and similar results have been reported for onion plants by other investigators (Randle and Lancaster, 2002). Shoot total sulfur concentrations in spring onion ranged from 0.15 to 0.44 %, which falls within the range of S concentrations in onion leaves and bulbs as reported by Randle (1992).…”
Section: Discussionsupporting
confidence: 79%
See 2 more Smart Citations
“…The EPY value, shoot and root TSC, and S content of shoots and roots of spring onion all increased with increasing S supply level in the substrate (Table 3). These results were expected and similar results have been reported for onion plants by other investigators (Randle and Lancaster, 2002). Shoot total sulfur concentrations in spring onion ranged from 0.15 to 0.44 %, which falls within the range of S concentrations in onion leaves and bulbs as reported by Randle (1992).…”
Section: Discussionsupporting
confidence: 79%
“…Therefore, it is suggested that effects other than the enhanced sulfur nutritional level due to mycorrhizal colonization may also play a role. The flavor precursors have been generally regarded to be involved in the defense reaction of plants against micro-organisms ( Randle and Lancaster, 2002). Wounded plants deliver available sulfur to synthesize defense-related substances by activating genes involved in the metabolism of sulfur (Harada et al, 2000).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In particular, sulphur is absorbed by the plant as sulphate, successively reduced and incorporated into cysteine, which is used for the synthesis of methionine and glutathione in the pathway of flavour biosynthesis (Anderson 1990;Randle, Lancaster 2002). Glutathione is the key metabolite for the biosynthesis of all ACSOs, starting from cysteine, glutamic acid, and glycine (Lancaster, Shaw 1989), and it serves as sulphur vehicle through several peptide pathways terminating in the synthesis of any flavour precursors (Randle, Lancaster 2002).…”
Section: Bulb Quality and Biological Propertiesmentioning
confidence: 99%
“…In particular, sulphur is absorbed by the plant as sulphate, successively reduced and incorporated into cysteine, which is used for the synthesis of methionine and glutathione in the pathway of flavour biosynthesis (Anderson 1990;Randle, Lancaster 2002). Glutathione is the key metabolite for the biosynthesis of all ACSOs, starting from cysteine, glutamic acid, and glycine (Lancaster, Shaw 1989), and it serves as sulphur vehicle through several peptide pathways terminating in the synthesis of any flavour precursors (Randle, Lancaster 2002). Notably, amino acids are also included in the flavour determinants and during maturation they are translocated from the senescing foliage to the bulb (Nilsson 1980); arginine and glutamine are the most abundant in onions (Hansen 2001), accounting for over 40% of the total free amino acids.…”
Section: Bulb Quality and Biological Propertiesmentioning
confidence: 99%